THE EFFECT OF RANGE OF MOTION (ROM) EXERCISES ON INCREASING MUSCLE STRENGTH IN NON-HEMORRHAGIC STROKE PATIENTS AT WONOSOBO ISLAMIC HOSPITAL - muhamad sahli; Candra Dewi Rahayu; Anisa Ell Raharyani (Jurnal Ilmiah Kesehatan, 2025)
Range of Motion (ROM) exercises are commonly used as a nursing intervention to prevent complications and enhance motor recovery in stroke patients. This study employed a case study design using an evidence-based practice approach involving two patients diagnosed with non-hemorrhagic stroke who experienced impaired physical mobility at Wonosobo Islamic Hospital. Active and passive ROM exercises were administered twice daily for three consecutive days. Muscle strength was assessed before and after the intervention using Manual Muscle Testing (MMT). The findings revealed an improvement in muscle strength in both patients following the ROM intervention. In the first patient, hand muscle strength increased from grade 1 to grade 2, while leg muscle strength improved from grade 4 to grade 5. In the second patient, both hand and leg muscle strength increased from grade 1 to grade 3. The results indicate that active and passive ROM exercises are effective in improving muscle strength in patients with non-hemorrhagic stroke. ROM exercises can be implemented as an independent nursing intervention to support motor function recovery and enhance patient mobility in clinical practice.